Pengaruh Model Pembelajaran Kaffah terhadap Karakter dan Kemampuan Pemecahan Masalah Peserta Didik pada Materi Momentum dan Impuls - Solihin Rahmat; Syahrial Ayub; Ni Nyoman Sri Putu Verawati (Mataram University, 2026)
This study aimed to analyze the effect of the Kaffah Learning Model on students’ character development and problem-solving abilities in the topic of momentum and impulse. The study employed a quasi-experimental method using a nonequivalent control group design. The research subjects were Grade XI students consisting of an experimental class and a control class. Data were collected through a problem-solving ability test and a student character questionnaire. Data analysis was conducted using normality tests, Levene’s test and Box’s M test for homogeneity, and hypothesis testing through Multivariate Analysis of Variance (MANOVA). The results showed that the Kaffah Learning Model had a significant effect on both problem-solving abilities and character development simultaneously. Students who participated in learning activities using the Kaffah Learning Model demonstrated better character development and higher problem-solving abilities compared to those who received conventional instruction. Therefore, the Kaffah Learning Model can be considered an effective alternative instructional model for enhancing students’ character and problem-solving abilities in physics learning.